2018
DOI: 10.1002/bab.1691
|View full text |Cite
|
Sign up to set email alerts
|

miR‐330‐3p promotes lung cancer cells invasion, migration, and metastasis by directly targeting hSOD2b

Abstract: Lung cancer is a serious threat to human health. Studies have revealed that human manganese superoxide dismutase (hSOD2) and miRNAs play an essential role in the metastasis process of lung cancer. However, the miRNAs that associated with hSOD2 and involved in metastasis, remain elusive. After databases analysis and dual luciferase reporter validation, we demonstrated that miR-330-3p expression inversely correlated with hSOD2b expression level, and that miR-330-3p directly targeted the 3'untranslated region (3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…It is a well‐accepted fact that the aberrant expression of miRNAs play significant roles in the carcinogenesis and progression of human cancers . Therefore, in‐depth understanding of the roles of miRNAs shall provide new dimension into molecular mechanism involved in the tumor formation and growth of cancer as well for the development of novel therapeutic strategies .…”
Section: Resultsmentioning
confidence: 99%
“…It is a well‐accepted fact that the aberrant expression of miRNAs play significant roles in the carcinogenesis and progression of human cancers . Therefore, in‐depth understanding of the roles of miRNAs shall provide new dimension into molecular mechanism involved in the tumor formation and growth of cancer as well for the development of novel therapeutic strategies .…”
Section: Resultsmentioning
confidence: 99%
“…It is well‐known that miRNA can affect the pathogenesis of various diseases by specifically targeting a certain mRNA . In order to further investigate the mechanisms of miR‐330‐3p on INS‐1 cells in GDM, in this study, we found that GCK was a target gene of miR‐330‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-330-3p can target the gene of program cell death 4 (PDCD4) to promote tumor [17]. MiR-330-3p is also related with metastasis and invasion of lung cancer, and glutamate receptor 3 (GRIA3) [18] and human manganese superoxide dismutase 2 (hSOD2) [19] are its two target genes. Researches found miR-330-3p is correlated with bad prognosis in breast cancer as well [20], in which miR-330-3p can target Collagen and Calcium Binding EGF Domains 1 (CCBE1) to promote cancer metastasis [21].…”
Section: Discussionmentioning
confidence: 99%